Fracking on YouTube: exploring risks, benefits and human values - Jaspal, Rusi; Turner, Andrew; Nerlich, Brigitte (White Horse Press, 2014)
Shale gas is a novel source of fossil fuel which is extracted by induced hydraulic fracturing, or “fracking.” This article examines the the socio-political dimension of fracking as manifested in the UK press at three key temporal points in the debate on the practice. Three newspaper corpora were analysed qualitatively using Thematic Analysis and Social Representations Theory. Three overarching themes are discussed: “April-May 2011: From Optimism to Scepticism”; “November 2011: (De-)Constructing and Re-Constructing Risk and Danger; “April 2012: Consolidating Social Representations of Fracking.” In this article, we examine the emergence and inter-relations between competing social representations, discuss the dynamics of threat positioning and show how threat can be re-construed in order to serve particular socio-political ends in the debate on fracking.